Conditions implying the vanishing of the Hamiltonian at the infinite horizon in optimal control problems - Atle Seierstad (University of Oslo, Department of Economics, 2002)
n an infinite horizon optimal control problem, the Hamiltonian vanishes at the infinite horizon, when the differential equation is autonomous. The integrand in the integral criterion may contain the time explicitly, but it has to satisfy certain integrability conditions. A generalization of Michels (1982) result is obtained.
Keywords: C61; 330; keyword infinite horizon; optimal control; Kontrolltheorie; Theorie